EFFECT OF EXECUTIVE COMPENSATIONS AND LEVERAGE ON TAX AGRESSIVITY (Study on Primary Sector of JASICA Listed on Indonesia Stock Exchange Period 2016-2020) - Dwi Urip Wardoyo; Novy Aryanty; Nisa Iswatini (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The company considers that the amount of tax borne can reduce profit. In addition, the benefits of paying taxes are not felt directly by the company, thus making the company feel dissatisfied. Therefore, the company will carry all illegal and legal methods to reduce the tax burden. The more often the company does tax planning to reduce the tax burden, the more aggressive the company is towards taxes.The purpose of this study was to determine and analyze the executive compensation and leverage on tax aggressiveness. This study uses primary sector of JASICA listed on the Indonesia Stock Exchange in 2016-2020. The method of determining the sample uses purposive sampling, which has obtained 13 companies for five years with 43 sample data. The data analysis method used is multiple linear regression analysis with the help of IBM SPSS 25 software. The results of this test showed that executive compensation and leverage have no effect on tax aggressiveness.